Kaposi sarcoma with musculoskeletal manifestations in a well-controlled HIV patient. (2019) - Verdecia, Jorge; Warda, Firas; Rechcigl, Kevin; Sokanovic, Mladen; Isache, Carmen
Abstract: We present here a case of relapsed HIV-related Kaposi Sarcoma (KS), manifesting as a plantar ulcer with underlying bone involvement in a patient with well-controlled HIV. Radiographic and magnetic resonance imaging of the patient's right foot showed bone destruction suggestive of osteomyelitis. However, when a bone biopsy was done, this was consistent with KS, without any signs of bone infection. Patient was initially diagnosed with KS four years prior. He was successfully treated at the time with doxorubicin, radiation therapy, and began HIV therapy. At the time of the KS recurrence, his HIV viral load was undetectable and his CD4 count was over 900 cells/uL (CD4 percentage of 42%). Musculoskeletal (MSK) involvement in KS is a rare manifestation of this disease. The argest series of skeletal KS in people living with HIV by Papanastasopoulos at el. showed a prevalence of only 1.1%. The radiological features of MSK-KS are generally lytic osseous lesions, but presentations may differ. Bone biopsy remains the gold standard for diagnosis, as many other infectious and neoplastic processes can mimic MSK-KS radiographically. In the era of highly active antiretroviral therapy, people living with HIV who are diagnosed with MSK-KS appear to have a substantially improved survival rate than previously described.